2015
DOI: 10.1177/2325967115s00150
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Are Patients At Diagnosing The Cause Of Their Knee Pain With The Help Of A Web-based Symptom Checker?

Abstract: Objectives:Researching medical information is the third most popular activity online, and there are a variety of web-based symptom checker programs available to the patient. A recent study has demonstrated that a web-based program can generate an accurate differential diagnosis in 89% of ambulatory patients with knee pain based on a history entered by the patient. Despite the regularity of online symptom checking, the authors are not aware of any study that has evaluated a patient's ability to self-diagnose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the help of the DSS, the diagnoses were given from the computer program, so that the patients do not have to choose the correct diagnoses. This is an important advantage, because Bison et al (2016) showed that only 58% of 328 patients who completed a symptom checker were able to identify the cause of their knee pain when they were given a list of 2 to 15 diagnoses [16].…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the DSS, the diagnoses were given from the computer program, so that the patients do not have to choose the correct diagnoses. This is an important advantage, because Bison et al (2016) showed that only 58% of 328 patients who completed a symptom checker were able to identify the cause of their knee pain when they were given a list of 2 to 15 diagnoses [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the accuracy of electronic symptom checkers for diagnosis and triage by using clinical case vignettes [21][22][23][24][25][26][27][28][29][30]. Vignettes appear to be a valid and comprehensive method that directly focuses on the process of care provided in actual clinical practice [31].…”
Section: Introductionmentioning
confidence: 99%